Lifestyle habits of adults during the COVID-19 pandemic lockdown in Cyprus: evidence from a cross-sectional study - Kolokotroni, Ourania; Mosquera, Maria C.; Quattrocchi, Annalisa; Heraclides, Alexandros; Demetriou, Christiana A.; Philippou, Elena (My University, 2021)
Background: The COVID-19 pandemic and the widespread adoption of virus control measures have inevitably disrupted efforts to address lifestyle risk factors for non-communicable diseases (NCD). This study aimed to explore the effects of COVID-19 lockdown on all lifestyle medicine pillars, namely diet, physical activity, sleep, stress, social support and use of risky substances. Methods: This was a cross-sectional study on a convenient sample of adults who resided in Cyprus during the Spring 2020 lockdown. Participants completed an anonymous online questionnaire comprised of six validated tools regarding the following lifestyle behaviours before and during lockdown: adherence to the Mediterranean diet, physical activity, stress and social support levels, sleep pattern and use of risky substances such as smoking and alcohol. Paired before and during lockdown comparisons for each lifestyle pillar were undertaken using Wilcoxon Signed-Rank test and Bowker symmetry Test where response was numerical (non-parametric data) and categorical respectively. Furthermore, stratified analyses for sociodemographic characteristics were performed. Results: Out of 745 participants, 74% were female and median age was 39 years. Overall participants reported significantly higher perceived stress score (22 v 25, p < 0.01), lower social support score (71 v 68, p < 0.001), and worse sleep quality score (4 v 5, p < 0.01) during lockdown. Mediterranean diet (MD) adherence was moderate and increased significantly only in those practicing religious fasting (score of 6 v 7, p < 0.01). Total minutes spent sitting increased (120 v 180, p < 0.01) although overall physical activity score did not significantly change. Smoking intensity increased during lockdown whilst frequency of alcohol consumption decreased (ptrend = 0.03 and < 0.01, respectively). Conclusion: Various lifestyle factors were adversely affected by the COVID-19 lockdown in Cyprus. Evidence from this study supports development of holistic lifestyle interventions during and following the pandemic to reduce short and long-term NCD risks by building on lifestyle behaviour strengths and addressing longstanding and emerging gaps and needs.
Keywords: Addictions; COVID-19; Coronavirus pandemic; Lifestyle; Lockdown; Mediterranean diet; Physical activity; Sleep; Social support; Stress